2003
DOI: 10.1021/nl034010k
|View full text |Cite
|
Sign up to set email alerts
|

Toward Large Arrays of Multiplex Functionalized Carbon Nanotube Sensors for Highly Sensitive and Selective Molecular Detection

Abstract: Arrays of electrical devices with each comprising multiple single-walled carbon nanotubes (SWNT) bridging metal electrodes are obtained by chemical vapor deposition (CVD) of nanotubes across prefabricated electrode arrays. The ensemble of nanotubes in such a device collectively exhibits large electrical conductance changes under electrostatic gating, owing to the high percentage of semiconducting nanotubes. This leads to the fabrication of large arrays of low-noise electrical nanotube sensors with 100% yield f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
638
0
6

Year Published

2004
2004
2018
2018

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 964 publications
(665 citation statements)
references
References 22 publications
21
638
0
6
Order By: Relevance
“…This makes CNT-FETs ideal systems for molecular sensing. It has been shown that coating the nanotubes with polymers can increase their selectivity in sensor applications, 5 and it is hoped that further functionalization will provide sensitivity to specific compounds, such as proteins or sugars, or even larger objects, such as viruses.…”
Section: Introductionmentioning
confidence: 99%
“…This makes CNT-FETs ideal systems for molecular sensing. It has been shown that coating the nanotubes with polymers can increase their selectivity in sensor applications, 5 and it is hoped that further functionalization will provide sensitivity to specific compounds, such as proteins or sugars, or even larger objects, such as viruses.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 The suppression of carrier backscattering brought about by the nanotube's band structure results in long mean free paths leading to ballistic transport and opens up the possibility of GHz and sub-THz applications. 3 Tailoring the intrinsic electronic properties of the CNT by choosing semiconducting or metallic CNTs has already led to the fabrication of field effect transistors 3 and sensors 4 for the former type of nanotube and interconnects 5 and field emission materials 6 for the latter.…”
mentioning
confidence: 99%
“…For in- 32 In the future, surface functionalization and/or large-scale multiplexing of nanotube sensors may be utilized to enable better specificity in the response and detection. 36 Additionally, the large surface-areato-volume ratio of nanotubes presents an ideal opportunity for energy storage applications, including supercapacitors and fuel cells. 39,40 Nanotubes also exhibit superb mechanical properties.…”
Section: Nano Focusmentioning
confidence: 99%